The Assessment of Components Affecting Social Capital in Rural Settlements (Case Study: Rural Settlements of Asalem District) - Ali Badri; Yasir Ramazannejad; Hasan Estehkam (جغرافیا و پایداری محیط)
Social capital is one of the new concepts in the social sphere and sociology. It is widely has been used by researchers in various fields. It deals with components such as trust, partnership, integrity and awareness and refers to the communications and links between members of a network as a valuable source. With the creation of norms and mutual trust, social capital helps the goals will be achieved. It is suitable ground for human and physical capital productivity and the way to achieve success. The research in this paper is a descriptive - analytical method and needed data is gathered using a questionnaire survey. T-test and regression analysis were used to test hypotheses. The results show the average social capital in the 15 studied villages is 29.3. In the other words the level of social capital at the village of Asalem is moderate. The social capital average is for women 3.169 and for men 3.336. That is, two sample means are equal and there is not social difference between men and women. Among the factors, social participation rates Beta, 0.477 has the highest effect on the formation of social capital. So 47.7% of the changes in social capital can be explained. Social awareness has the lowest level with Beta 0.145